2019
DOI: 10.1101/cshperspect.a032458
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Analysis of Reverse Transcriptase Enzymes

Abstract: The original discovery of enzymes that synthesize DNA using an RNA template appeared to contradict the central dogma of biology, in which information is transferred, in a unidirectional way, from DNA genes into RNA molecules. The paradigm-shifting discovery of RNA-dependent DNA polymerases, also called reverse transcriptases (RTs), reshaped existing views for how cells function; however, the scope of the impact RTs impose on biology had yet to be realized. In the decades of research since the early 1970s, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…The dynamic behavior of RT ipping and sliding over a dsDNA or an RNA/DNA substrate have been observed by single-molecule FRET studies. 14,15,26 Our current crystallization requires Cd 2+ ions and the structure revealed that two active site Mg 2+ ions in the N complex have been replaced by two Cd 2+ ions (Fig. 1f); signi cantly strong scatterer Cd 2+ ions that has 46 electrons compared to Mg 2+ ions that has 10 electrons produced strong electron density peaks;…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The dynamic behavior of RT ipping and sliding over a dsDNA or an RNA/DNA substrate have been observed by single-molecule FRET studies. 14,15,26 Our current crystallization requires Cd 2+ ions and the structure revealed that two active site Mg 2+ ions in the N complex have been replaced by two Cd 2+ ions (Fig. 1f); signi cantly strong scatterer Cd 2+ ions that has 46 electrons compared to Mg 2+ ions that has 10 electrons produced strong electron density peaks;…”
Section: Resultsmentioning
confidence: 89%
“…In general, the transient states have been considered as important targets for drug design 13 , and there may exist unidenti ed transient states of HIV-1 RT that can be valuable for discovering new classes of drugs. During the polymerization process, RT has been shown to slide over its substrate by singlemolecule FRET studies, 14,15 which indicates potential for the existence of transient states, however, no transient state has been structurally characterized. In this study, we crystallized HIV-1 RT/dsDNA in a new crystal form with two copies of the complex present in the crystallographic asymmetric unit; in one, the primer 3'-end nucleotide occupies the N site representing the pre-translocation complex (N complex) and in the other copy, RT slides ahead of dsDNA such that the primer 3' terminus occupies P-1 site (P-1 complex).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic behavior of RT flipping and sliding over a dsDNA or an RNA/DNA substrate have been observed by single-molecule FRET studies. 14,15,26 Our current crystallization requires Cd 2+ ions and the structure revealed that two active site Mg 2+ ions in the N complex have been replaced by two Cd 2+ ions (Fig. 1f); significantly strong scatterer Cd 2+ ions that has 46 electrons compared to Mg 2+ ions that has 10 electrons produced strong electron density peaks; Cd 2+ ions were unambiguously located in the structure.…”
Section: + Ions Arrest N Complex and Dna:dna Crystal Contact Stabilizes P-1 Complexmentioning
confidence: 78%
“…In general, the transient states have been considered as important targets for drug design 13 , and there may exist unidentified transient states of HIV-1 RT that can be valuable for discovering new classes of drugs. During the polymerization process, RT has been shown to slide over its substrate by single-molecule FRET studies, 14,15 which indicates potential for the existence of transient states, however, no transient state has been structurally characterized. In this study, we crystallized HIV-1 RT/dsDNA in a new crystal form with two copies of the complex present in the crystallographic asymmetric unit; in one, the primer 3’-end nucleotide occupies the N site representing the pre-translocation complex (N complex) and in the other copy, RT slides ahead of dsDNA such that the primer 3’ terminus occupies P-1 site (P-1 complex).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of consecutive copies of telomeric repeats involves extremely complex and delicate processes, including dissociation, translocation and realignment of the RNA-DNA hybrid ( 31 ). Telomerase must undergo extensive domain or motif rearrangements for each round of telomere addition to accomplish these tasks ( 58 ). However, such structural mobility remains speculative and direct structural evidence is still lacking ( 12 ).…”
Section: Discussionmentioning
confidence: 99%